Al-Mustadh'afin: Reflection of the Qur'an on Social Inequalities - Muhammad Alwi; Achmad Abubakar; M Ilham; Mikdar Rusdi (IAIN Padangsidimpuan, 2022)
This article aims to reveal the reflection of the Qur'an on the oppressed group in the context of social inequality. Using the descriptive analytical approach in the various literature related to the subject of this research, whether in the form of primary sources such as the Qur’an and interpretations, as well as secondary sources in the form of books and articles, the results of the study found that the Qur'an's reflection of al-Mustadh'afin refers to a marginalized community, weak, oppressed, and powerless groups both culturally and structurally. In the context of social inequality, the poor, orphans, beggars, and slaves are al-Mustadh'afin groups. The effort to liberate the al-Mustadh'afin from all forms of discrimination, oppression, and exploitation that leads to social inequality is a vision of Islamic teachings. In the context of the Indonesian state, Pancasila and the 1945 Constitution are the two supporting pillars that are in line with the spirit of the Al-Qur'an's alignment with al-Mustadh'afin. Thus, the defense of al-Mustadh'afin in the context of social inequality can be done by maximizing the role of government, agencies, and social institutions.